Monte Carlo FLUKA Simulation of Gamma Backscattering for Rebar Detection in Reinforced Concrete with Basaltic Aggregates - Alexandre Osni Gral Iori; Emerson Mario Boldo (Atoms, 2025)
Compton backscattering is a versatile non-destructive technique for material characterization and structural evaluation in reinforced concrete. This methodology enables a single-sided inspection of large structures—which is particularly useful where only one side of the material is accessible for examination—is relatively inexpensive, and can be made portable for field applications. This study aims to assess the influence of basaltic coarse aggregates on the accurate localization and dimensioning of rebar in reinforced concrete using the gamma-ray Compton backscattering technique at two distinct incident photon energies—59.5 keV and 1170 keV. The analysis was performed through Monte Carlo simulations using the FLUKA code, providing insights into the feasibility and limitations of this non-destructive method for structural evaluation. Both photon energies successfully detected the rebar embedded at a 3 cm depth in mortar, achieving a good spatial resolution and contrast, despite the presence of a significant amount of iron oxide within the aggregate. Among the evaluated sources, 60Co yielded the highest contrast and count values, demonstrating its potential for rebar detection at greater depths within concrete structures. The single-sided Compton scattering technique proved to be effective for the investigated application and presents a promising alternative for the non-destructive assessment of real-world reinforced concrete structures.